2015
DOI: 10.1001/jamapediatrics.2014.3280
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Trial of Health Care Technologies to Improve Adherence to Pediatric Asthma Treatment

Abstract: clinicaltrials.gov Identifier: NCT00958932.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 19 publications
2
96
2
Order By: Relevance
“…The asthma diary entry rate was exceptionally high (93.5% on average) in the present study. We also found that daily medication administration rates were relatively high relative to those of other reports (Bender et al, ; Otsuki et al, ), with 25 caregivers (55.6%) reporting total medication compliance and 20 (44.4%) describing being unable to achieve full compliance with medication regimens. It is important to note here; however, that a social desirability bias may have driven some participants to answer more favorably when asked about medication compliance or to complete diary entries.…”
Section: Discussionsupporting
confidence: 42%
“…The asthma diary entry rate was exceptionally high (93.5% on average) in the present study. We also found that daily medication administration rates were relatively high relative to those of other reports (Bender et al, ; Otsuki et al, ), with 25 caregivers (55.6%) reporting total medication compliance and 20 (44.4%) describing being unable to achieve full compliance with medication regimens. It is important to note here; however, that a social desirability bias may have driven some participants to answer more favorably when asked about medication compliance or to complete diary entries.…”
Section: Discussionsupporting
confidence: 42%
“…on May 11, 2018. by guest www.bloodjournal.org From better palatability may also improve adherence among pediatric patients and should be developed. Other methods to improve adherence, such as direct supervision or various reminder systems, 74 may be needed in patients with suboptimal responses to TKIs. Another factor that needs to be considered is the cumulative cost of TKI therapy in children who may need decades of treatment, although this may become less of an issue in the near future with the introduction of generic products.…”
Section: Pediatric CML May Require a Different Approach To Tki Treatmentmentioning
confidence: 99%
“…Although pragmatic drug trials in children are generally lacking, recent interventional pragmatic trials provide some insight into trial execution. The Breathe Well study was a pragmatic interventional study designed to evaluate adherence in pediatric asthma by comparing usual care to speech recognition calls using personalized EHR information (eg, child's name and sex, physician name, medication name) when inhaled corticosteroid refills were due . The intervention resulted in a 25% increase in adherence (9% absolute difference); however, there was no observed difference in sick visits or β‐agonist use .…”
Section: Clinical Trial Optimizationmentioning
confidence: 99%